Surface structure and electron transfer dynamics of the self-assembly of cyanide on Au{111} - Guttentag, Andrew I.; Wächter, Tobias; Barr, Kristopher K.; Abendroth, John M.; Song, Tze-Bin; Sullivan, Nichole F.; Yang, Yang; Allara, David L.; Zharnikov, Michael; Weiss, Paul S. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
A vibronic resonance between Au{111} surface states and adsorbed CN vibrations has been predicted, which we target for study. We have formed stable monolayers of cyanide on Au{111} and observe a hexagonal close-packed lattice with a nearest neighbor distance of 3.8 ± 0.5 Å. Cyanide orients normal to the surface attached via a Au-C bond. We show that the substrate-molecule coupling is particularly strong, leading to ultrafast electron transfer from the cyanide molecules to the Au{111} substrate as measured by resonant Auger spectroscopy using the core-hole clock method. The CN/Au{111} system is a simple example of a strongly interacting adsorbate-substrate system and will be the subject of a number of further studies, as discussed.